Perturbatively exact supersymmetric partition functions of ABJM theory on Seifert manifolds and holography - Junho Hong (Journal of High Energy Physics)
Abstract We undertake a comprehensive analysis of the supersymmetric partition function of the U(N) k × U(N) −k ABJM theory on a U(1) fibration over a Riemann surface, evaluating it to all orders in the 1/N-perturbative expansion up to exponentially suppressed corrections. Through holographic duality, our perturbatively exact result is successfully matched with the regularized on-shell action of a dual Euclidean AdS4-Taub-Bolt background incorporating 4-derivative corrections, and also provides valuable insights into the logarithmic corrections that emerge from the 1-loop calculations in M-theory path integrals. In this process, we revisit the Euclidean AdS4-Taub-Bolt background carefully, elucidating the flat connection in the background graviphoton field. This analysis umambiguously determines the U(1) R holonomy along the Seifert fiber, thereby solidifying the holographic comparison regarding the partition function on a large subclass of Seifert manifolds.